Influence of Nitrogen Atom on Alkynyl Benzoate Donor Reactivity: 3-(Phenyl Ethynyl) Picolinates as Stable and Reactive Glycosyl Donors Towards Stereoselective Glycoside Bond Formation - Lenka, Rajesh; Moktan, Sangay; Rotta, Mahendra K; Kumar, Pavan K. (Synlett)
We have demonstrated the development of 3-(phenyl ethynyl) picolinates as new stable and reactive glycosyl donors activated by Au [I] catalysis. This study aims to understand the reactivity differences between a simple ortho-phenylethynyl benzoate donor versus a phenyl ethynyl picolinate donor under gold (I) catalysis.The study establishes that, contrary to the general expectation, the picolinate donors are more reactive than the corresponding orthobenzoate alkyne donors, presumably due to the thermodynamic stability of the leaving group under the catalytic conditions. In addition, even with the presence of a Lewis basic nitrogen atom, the alkyne activation by gold (I) is the predominant mode of activation of the leaving group, due to the soft character of gold, leading to the cyclic product and not via the Lewis acidic coordination of gold with nitrogen and the ester oxygen. However, despite the alkynyl activation, the pyridine moiety fails to behave as a directing group via H-bonding with the incoming alcohol nucleophile. This study, however, paves the way for further exploration in this direction, leading to a simpler donor providing S N 2-type alkyne activation.